Campus Planning and Design across Southeast Asia: A Scoping Literature Review from 2002-2022 - Mansor, Sabariah; Ahmad, Raziah; Abdullah, Jamalunlaili; Gai, Ardiyanto Maksimilianus (Environment-Behaviour Proceedings Journal, 2023)
As Southeast Asia continues to experience rapid urbanization, ensuring sustainable development in higher education campuses is becoming increasingly crucial. This paper presents a systematic literature review of 52 relevant research articles from 2002-2022. By analyzing the existing literature, this study aims to explore key themes in campus and planning design across Southeast Asia while incorporating Sustainable Development Goals (SDGs) as contextualizing background. Findings suggest sustainable and inclusive campus as dominant themes which significant to promote student well-being and academic success while enhancing environmental responsibility in Southeast Asia’s campus.